2015
DOI: 10.1093/ntr/ntu265
|View full text |Cite
|
Sign up to set email alerts
|

Social Branding to Decrease Lesbian, Gay, Bisexual, and Transgender Young Adult Smoking

Abstract: Introduction: Lesbian, gay, bisexual, and transgender (LGBT) individuals are more likely to smoke than the general population. This study evaluated a Social Branding intervention, CRUSH, which included an aspirational brand, social events, and targeted media to discourage smoking among LGBT young adults in Las Vegas, NV. Methods: Cross-sectional surveys (N = 2,395) were collected in Las Vegas LGBT bars at 2 time points 1 year apart. Multivariate logistic regressions examined associations between campaign expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 26 publications
(28 reference statements)
1
71
2
Order By: Relevance
“…In addition, while an intervention targeting the Partier peer crowd in Oklahoma was not associated with a significant change in smoking prevalence overall, Partiers who recalled HAVOC had decreased odds of daily smoking and unchanged nondaily smoking, while Partiers and non-Partiers who did not recall HAVOC had increased odds of smoking over time [20]. Further exploring potential factors associated with Social Branding interventions in bars and smoking prevalence, an intervention focused on Lesbian, Gay, Bisexual, or Transgender (LGBT) bar culture in young adults in Las Vegas, Nevada, found that higher intervention exposure was associated with decreased smoking among individuals who understood the smoke-free message of the intervention [21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while an intervention targeting the Partier peer crowd in Oklahoma was not associated with a significant change in smoking prevalence overall, Partiers who recalled HAVOC had decreased odds of daily smoking and unchanged nondaily smoking, while Partiers and non-Partiers who did not recall HAVOC had increased odds of smoking over time [20]. Further exploring potential factors associated with Social Branding interventions in bars and smoking prevalence, an intervention focused on Lesbian, Gay, Bisexual, or Transgender (LGBT) bar culture in young adults in Las Vegas, Nevada, found that higher intervention exposure was associated with decreased smoking among individuals who understood the smoke-free message of the intervention [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The multi-component intervention strategy has been further described previously and is summarized in Figure A (Online Supplement) [19,20]. Social Branding interventions targeting smoking behavior have been implemented previously in bars in San Diego, California [19], Oklahoma City, Oklahoma [11], and Las Vegas, Nevada [1921], with decreases in smoking prevalence noted in different populations of young adults. We aimed to evaluate young adult smoking prevalence over the course of 3 years during a Social Branding intervention implemented in bars and nightclubs in a different city, Albuquerque, New Mexico, and also to explore potential mediators in the association between the intervention and smoking status.…”
mentioning
confidence: 99%
“…Participants were recruited using time location sampling, 21 a technique that has been used with “hard to reach” populations, and the methods used here have been described previously. 22,23 Similar to past tobacco marketing strategies in bars, the research team worked with a marketing consultant with expertise in young adult bar/nightclub events to identify party promoters, bartenders, DJs, and other entertainers in the scene. Interviews were conducted with these opinion leaders in each city to generate a census of the most popular young adult bars/nightclubs.…”
Section: Methodsmentioning
confidence: 99%
“…[22,37,38] Tailored interventions need to articulate a nuanced understanding of cultures, communities and identities. [39] Interventions that engage directly with the meaning of smoking in LGBT culture and venue-based socialising, as one social-branding program in the US did [40] or disrupting its place as a marker of identity, may be more salient. [41] Our findings also suggest value in developing ways for younger LBQ women to connect with peers without smoking as an aid to connection.…”
Section: Discussionmentioning
confidence: 99%